2022
DOI: 10.1021/acsomega.2c00038
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Molecular Dynamics Simulation Study for Preferring Coal Dust Wetting Agents

Abstract: To improve the efficiency of coal dust removal by water spray technology, the addition of wetting agents in water becomes the main dust removal method. The influence of sodium dodecyl sulfate (SDS), sodium dodecyl sulfonate (SDDS), and sodium dodecylbenzene sulfonate (SDBS) on the wettability of coal dust is studied by experimental and molecular dynamics (MD) simulation. Measurement of the contact angle and surface tension was accomplished via relevant experiments for the three wetting agents, and their adhesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…SAILs have thermal stability and good catalytic activity. There is no secondary pollution, and they are not flammable. Surface–active ionic liquids can reduce the interfacial tension of aqueous solutions, affecting the pore structure of coal and improving dust reduction efficiency. Scientists find that wettability is related to the anion, cation, and concentration of ionic liquids. , Gao et al used an infrared spectroscopy test to study the impact of cations and anions on functional groups found that anions and cations have different effects on the structure of coal . Zhou et al established an analytical mechanism for coal–surfactant wettability evaluation by simulating the effect of surfactants on coal microcrystalline structures and found that ether groups and hydroxyl groups affect the wetting effect .…”
Section: Introductionmentioning
confidence: 99%
“…SAILs have thermal stability and good catalytic activity. There is no secondary pollution, and they are not flammable. Surface–active ionic liquids can reduce the interfacial tension of aqueous solutions, affecting the pore structure of coal and improving dust reduction efficiency. Scientists find that wettability is related to the anion, cation, and concentration of ionic liquids. , Gao et al used an infrared spectroscopy test to study the impact of cations and anions on functional groups found that anions and cations have different effects on the structure of coal . Zhou et al established an analytical mechanism for coal–surfactant wettability evaluation by simulating the effect of surfactants on coal microcrystalline structures and found that ether groups and hydroxyl groups affect the wetting effect .…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies aimed at improving the wettability of coal seams and gas extraction efficiency concentrated on water injection and gas injection displacement. Research on water injection focused on the use of surfactants. Surfactants are the main wetting agents in improving wettability, and surface tension is a key parameter for their effectiveness. Jiang et al found that OP-10 surfactant solutions had the best effect on improving coal wettability based on surface tension and contact angle measurements of different wetting agents. , Several studies have explored the effect of wetting agents in different proportions or combined with other materials to improve the wettability of coal seams. , For instance, Zou et al added water-based SiO 2 nanofluids to the wetting agent solution and proposed a water injection method for coal seam improvement. , Molecular simulation software has been employed by some scholars to investigate the mechanism of surfactant effect on enhancing coal seam wettability. ,, In addition, the COMSOL simulation software was used to develop a coupled damage model during water injection to increase gas extraction rates. , Studies on gas injection displacement for improving gas extraction rates can be categorized into two types: using gases with strong adsorption capacity or gases that can break the dynamic balance of coal seam gas. CO 2 -enhanced coalbed methane (CO 2 -ECBM) technology is essential to ensure energy security and achieve the “dual carbon” goal. This technology is crucial for achieving the low-carbon, clean, and efficient utilization of coal-based fossil energy.…”
Section: Introductionmentioning
confidence: 99%
“…Improving coal dust wettability by adding surfactants is a research focus. Sun et al 3 analyzed the wetting process of bituminous coal by SDS, SDBS, and SDDS through experiments and simulations and pointed out that the wetting efficiency of three surfactants for bituminous coal is: SDS > SDDS > SDBS. Shi et al 4 studied the synergistic effect between noncationic surfactants and pointed out that the addition of noncationic surfactants reduced the electrostatic repulsion between anionic surfactants, thus increasing the adsorption density of coal surfactants.…”
Section: Introductionmentioning
confidence: 99%
“…Improving coal dust wettability by adding surfactants is a research focus. Sun et al . analyzed the wetting process of bituminous coal by SDS, SDBS, and SDDS through experiments and simulations and pointed out that the wetting efficiency of three surfactants for bituminous coal is: SDS > SDDS > SDBS.…”
Section: Introductionmentioning
confidence: 99%